EVALUATION OF THE RELIABILITY OF «GANZ» PORTAL CRANE MECHANISMS - STRELBITSKIY, Victor (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Portal cranes are widely used in various ports for transhipment operations.  However, today in the river and sea ports of Ukraine, more than 88% of cranes have fulfilled the standard service life and continue to be operated. Since portal cranes are the main link in the technological process, therefore, the productivity of Port lines depends on their reliable and trouble-free operation. The analysis of statistical data shows that the processing and long-term operation of portal cranes in the mode of intense cyclic loading leads to the formation of fatigue defects and the subsequent failure of their components and accidents [1-9]. Therefore, ensuring safe and reliable operation is one of the main tasks in the design, modernization and operation of cranes. The analysis of works] showed that the reliability of portal crane mechanisms that have been soldered for more than 35 years in sea and river ports has not been sufficiently studied. For research, 24 identical Ganz cranes with a lifting capacity of 16 tons were selected, which operate in clamshell mode in sea and river ports. The analysis uses information contained in the respective maintenance and repair logs of the respective cranes from 2008 to 2021.Data analysis shows that the greatest number of failures is observed in the mechanisms of movement, lifting, changing the boom departure and metal structures of cranes. It should be noted that up to 75% of all time is spent on restoring the operation of reducers. The reasons for the failure of movement mechanisms are: wear of gears and shafts of gearboxes, destruction and wear of bearings in gearboxes, cracks in gearbox housings. The failures of the mechanisms for changing the reach of the boom are caused by wear of the teeth of the racks and gears, bearings and gear housings of the mechanism.
Keywords: portal crane; Ganz; mechanism; failure; reliability